Artistic Level of Mastering the Mstyora Lacquer Miniature Painting in Higher Education: Typical Difficulties and Ways of Their Overcoming - V. Y. Borisova (Научный диалог)
Analytical review of the typical difficulties of students of secondary vocational education and higher education (bachelor course) in the study of Mstyora lacquer miniature painting at the creative level of development is presented. It is noted that the artistic activity of young professionals, expressing themselves in creative activity and affecting the current state of the art of Mstyora, is determined in general by iconographic direction. The research urgency is caused by necessity of revealing the ways of preservation and development of unique art of Mstyora lacquer miniature painting, which is an integral part of the national artistic culture, in the framework of the professional education in this field. It is noted that in secondary vocational education one cannot in full formulate those qualities which will enable the graduate to independently solve the task of creating a holistic artistic image. Therefore, the continuation of education at bachelor course is considered a good opportunity for creative development of the future specialist. However, the author shows that at this time there is a trend in downwarding students’ interest to achieve the highest point of creative development. The causes of the problem and ways of its overcoming are discussed: removal or leveling.